The Influence of Government Expenditure, Domestic Investment, and Sustainable Development on Inclusive Economic Growth in Sumatra Provinces (2019-2023) - Nur Azima; Etik Umiyati; Putri Intan Suri (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
Inclusive economic growth remains a critical challenge across Sumatra’s provinces, where disparities in welfare, infrastructure, and environmental quality persist. Focusing on ten provinces on the island of Sumatra between 2019 and 2023, this research assesses how inclusive economic growth is influenced by government social assistance expenditure, domestic investment (PMDN), and sustainable development (proxied by HDI and IKLH). Employing panel data regression with the Random Effects Model (REM) as the adjudicated specification, the empirical outcomes reveal that, under partial estimation, all independent variables exert a discernible bearing upon inclusive economic growth. Conversely, under simultaneous estimation, solely the Human Development Index (HDI) manifests as a statistically consequential determinant, whilst social assistance expenditure, domestic investment, and the Environmental Quality Index (IKLH) yield no appreciable influence on inclusive economic growth across the provinces under scrutiny. These findings suggest that human capital development plays a more dominant role than fiscal and investment variables in driving inclusive growth. Policymakers in Sumatra should prioritize sustainable human development to reduce inequality and enhance economic participation across provinces.